A Study of the Learning Achievement and Attitude in Mathematics of Grade 12 Student Using the Cooperative Learning Management with Student Teams Achievement Division (STAD) and KWDL Technique - Jirachotdaecho, Ghirana; Khum-un, Seree (Ratchaphruek Journal, 2023)
The purposes of this research were to: (1) Compare the learning achievement of grade 12 students receiving the cooperative learning activities (STAD) with KWDL technique with the criteria of 70 percent; (2) Study the effectiveness index of mathematics learning activities by using the cooperative learning activities (STAD) with KWDL technique; and (3) Study the students’ attitude towards mathematics learning who learned by using cooperative learning activities (STAD) with KWDL technique. The sample was comprised of 44 students in grade 12 of the Demonstration School of Ramkhamhaeng University by cluster random sampling. The research instruments were the achievement test and the attitude test. The effectiveness index, percentage, mean, standard deviation of items, and one-sample t-test were used to analyze the data. The findings revealed that: (1) The achievement of grade 12 students receiving the cooperative learning activities (STAD) with KWDL technique was higher than the criterion of 70 percent with a statistical significance of .05; (2) The effectiveness index of cooperative learning activities (STAD) with KWDL technique was 0.5562; (3) The students who learned by using cooperative learning activities (STAD) with KWDL technique had good attitude towards learning mathematics.